Meta-analysis of supervisor support and postgraduate creativity: evidence from a sample of Chinese students - Chang, Qiaoli; Han, Hui; Hu, Dexin (Frontiers in Education, 2025)
IntroductionWith the growing number of Chinese postgraduate students, enhancing their creativity has become a pressing issue in Chinese higher education. This meta-analysis aimed to investigate the relationship between supervisor support and postgraduate creativity using a sample of Chinese students and to explore potential moderating variables.MethodThe study incorporated 62 primary studies involving 51,640 Chinese graduate students.ResultsThe results revealed that supervisor support was significantly and positively associated with postgraduate creativity. Meta-regression and subgroup analyses showed that while postgraduate students' gender did not moderate this relationship, degree level, academic discipline, and type of higher education institution did. Specifically, supervisor support had a stronger correlation with creativity at the master's level compared to the doctoral level. Similarly, the relationship was stronger in the scientific and technical fields than in the humanities, social sciences, medical sciences, and agriculture. Additionally, supervisor support was more positively correlated with creativity in general universities compared to key universities.ConclusionThese findings offer valuable insights for further research on the impact of supervisor support on postgraduate creativity.